Interface-free capillary electrophoresis-mass spectrometry system with nanospray ionization-Analysis of dexrazoxane in blood plasma - Tycova, Anna; Vido, Marek; Kovarikova, Petra; Foret, Frantisek (Journal of chromatography. A, 2016)
The newly developed interface-free capillary electrophoresis-nanospray/mass spectrometry system (CE-nESI/MS) was applied for rapid analysis of the cardioprotective drug dexrazoxane and its hydrolysed form ADR-925 in deproteinized blood plasma samples. The aim of this study was to test the simplest possible CE-nESI/MS instrumentation for analyses of real samples. This interface-free system, utilizing single piece of a narrow bore capillary as both the electrophoretic separation column and the nanospray emitter, was operated at a flow rate of 30nL/min. Excellent electrophoretic separation and sensitive nanospray ionization was achieved with the use of only one high voltage power supply. In addition, hydrophobic external coating was developed and tested for additional stability of the nanospray ionization. To our knowledge this is the first study devoted to the analysis of dexrazoxane and ADR-925 by capillary electrophoresis-mass spectrometry.
Keywords: glycin; Capillary electrophoresis; Glycine; hmotnostní spektrometrie s elektrosprejovou ionizací; Dexrazoxane; Mass spectrometry; Ethylenediamines; Nanospray; dexrazoxan; Blood Chemical Analysis; Electrophoresis, Capillary; Spectrometry, Mass, Electrospray Ionization; biochemická analýza krve; Interface; elektroforéza kapilární; Hydrophobic coating; ethylendiaminy